CONCEPT OF CONTROL AND PREVENTIVE ACCOMPANYING MEASURES FOR IMPROVING THE RESOURCE POTENTIAL IN RESIDENTIAL CONSTRUCTION (INNOVATIVE ECONOMY, 2022)
Gumenna-Derii M.V. CONCEPT OF CONTROL AND PREVENTIVE ACCOMPANYING MEASURES FOR IMPROVING THE RESOURCE POTENTIAL IN RESIDENTIAL CONSTRUCTIONPurpose. The aim of the article is to study the concept of control and preventive and accompanying measures to improve its resource potential on the example of construction enterprises.Methodology of research. General scientific and specific research methods were used during the article, namely: graphic - to study the concept of resource control in construction; analytical - to analyse the financial resources needed to restore destroyed residential buildings; inductions and deductions - for the study of types of control in national practice; monographic - for researching the scientific works of scientists in this field; prognostic - for the formation of prospects for the development of control as prerequisites for preventive and accompanying measures.Findings. It has been proven that the application of preventive and accompanying measures will improve the system of control over material, technical and financial resources. It is substantiated that the concept of control is quite broad, because it includes the purpose, tasks, objects, subjects, functions, types, methodology and organization of control, which need improvement and have their own specificity in residential construction. It was found that the prospects for improving control are a number of measures related to the organization of documentation, improvement of the internal control system and automation in terms of material, technical and financial resources.Originality. The author substantiated theoretical provisions and developed recommendations for improving the concept of control over material, technical and financial resources for the purpose of effective management of construction projects.Practical value. The author's proposals can be used by construction enterprises, because due to the improvement of the quality of preventive and accompanying control in the practical activities of enterprises, fewer errors will occur when conducting various types of control, management accounting and reporting will improve, and the construction object will be put into operation in a timely manner.Key words: preventive control, accompanying control, housing construction, material and technical resources, financial resources.
Keywords: preventive control; accompanying control; housing construction; material and technical resources; financial resources.